PENGEMBANGAN MEDIA INTERACIVE STORY BOOK SEBAGAI EDUKASI PEMAHAMAN NILAI PANCASILA PESERTA DIDIK SDN KARANGKEBAGUSAN - Miratus Shoofiyah; Hamidaturrohmah Hamidaturrohmah (Universitas Tribhuwana Tunggadewi, 2025)
The rapid development of science and technology in this era of globalization makes it necessary to instill the values of Pancasila. This study aims to develop an interactive storybook learning media, measure the feasibility and practicality of the media, as well as assess students' understanding of Pancasila values. The research uses the Research and Development (RnD) method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. This study was conducted in the fifth grade at SDN Karangkebagusan. Data collection techniques included interviews, needs analysis, validation by media and material experts, responses from teachers and students, and tests. The research instruments consisted of a needs analysis questionnaire, media and material expert validation sheets, teacher and student response questionnaires, and test questions. The results show that the development of the interactive storybook media is feasible to use, with media validation showing an average percentage score of 94%, and material validation obtaining an average percentage score of 90%, both categorized as very feasible. Teacher responses to this media reached an average percentage score of 96%, while student responses reached 93%. The students' understanding, measured through the administered test, achieved an average score of 80, with the highest score of 90 and the lowest score of 75. This indicates that the use of the Interactive Storybook media can help students understand the values of Pancasila in a more interactive and engaging way.